The microstrop step discontinuity analysis by transverse resonance technique: method of boundary value problem algebraization - Рассохіна, Ю.В.; Крижановський, В.Г. (Radiotekhnika, 2019)
The two-dimensional eigenfunctions of the magnetic and electric vector potentials are constructed in the form of their expansion in series of Chebyshev orthogonal polynomials of 1st and 2nd kind to describe the current density in a strip transmission line with a step discontinuity of finite length. The solving boundary value problems algorithms for the resonant frequencies of a symmetric microstrip resonator with a capacitive section in it are developed and investigated on convergence. The account of the field behavior on thin edge in a nonuniform strip line provides the fast convergence of algorithm and small orders of solvable linear algebraic equations system. As examples of application, the transverse resonance method was used to calculate the scattering characteristics on 2-plane symmetric discontinuities consisting of a capacitive section of a microstrip line and slot resonators of complex shape in its ground plane.